Effects Exerted by Transcriptional Regulator PcaU from Acinetobacter sp. Strain ADP1 - Trautwein, Gaby (American Society for Microbiology, 2001)
Protocatechuate degradation is accomplished in a multistep inducible catabolic pathway in Acinetobacter sp. strain ADP1. The induction is brought about by the transcriptional regulator PcaU in concert with the inducer protocatechuate. PcaU, a member of the new IclR family of transcriptional regulators, was shown to play a role in the activation of transcription at the promoter for the structural pca genes, leaving open the participation of additional activators. In this work we show that there is no PcaU-independent transcriptional activation at the pca gene promoter. The minimal inducer concentration leading to an induction response is 10(−5) M protocatechuate. The extent of expression of the pca genes was observed to depend on the nature of the inducing carbon source, and this is assumed to be caused by different internal levels of protocatechuate in the cells. The basal level of expression was shown to be comparatively high and to vary depending on the noninducing carbon source independent of PcaU. In addition to the activating function, in vivo results suggest a repressing function for PcaU at the pca gene promoter in the absence of an elevated inducer concentration. Expression at the pcaU gene promoter is independent of the growth condition but is subject to strong negative autoregulation. We propose a model in which PcaU exerts a repressor function both at its own promoter and at the structural gene promoter and in addition functions as an activator of transcription at the structural gene promoter at elevated inducer concentration.